YOUNG ADULT CAREGIVER NEEDS AND PREFERENCES: A CROSS-SECTIONAL EXPLORATION OF DEMENTIA CAREGIVERS. (11th November 2018) - James, N
Abstract: Young adult caregivers, while making up a significant portion of informal caregivers, are often scarce or non-existent within research and intervention samples of caregivers. This disparity in sampling is more pronounced for caregivers of older adults, especially those experience Alzheimer's disease or other dementia-related difficulties. The presented study compared burden and circumstance variables among young adult, middle aged, and older adult caregivers (N = 285) in addition to developmental indicators among caregiver and matched non-caregiver young adult peers (n = 225). Findings indicate that young adult caregivers take on similar caregiving roles and report similar levels of burden as other-aged caregivers. However, young adult caregivers reported unique life stressors (e.g., childrearing, work obligations, and commuting to provide care). Additionally, when compared to demographically matched-peers, young adult caregivers were more likely to work part-time and earn a substantially lower yearly income compared to non-caregiving peers. Of importance, these additional burden factors do not explain the overwhelming lack of young adults in research samples. Implications and actionable changes for this unique population are outlined.